Etnomedisin Tetumbuhan Obat Tradisional Suku Serawai di Seluma, Bengkulu - Muhammad Adeng Fadila; Nunik Sri Ariyanti; Eko Baroto Walujo (PendIPA Journal of Science Education, 2020)
[Ethnomedicinal plants of Serawai Tribe in Seluma, Bengkulu, Indonesia] Knowledge on traditional medicinal plants is generally closely related to the biodiversity, social, and culture of community. This study aims to inventory the diversity of plants that are recognized and used as traditional medicine by Tribe Serawai, and to analyze the local user value index (LUVI) of those medicinal plants. The study was conducted in four villages from four sub-districts in Seluma District, Bengkulu Province. Structured questionnaire and opened-answers questionnaire was applied for interviewing seven key informants and 232 respondents. Collecting and identifying specimen was conducted to confirm scientific name of the plant. The LUVI was calculated based on the score determined by respondents in a Focus Group Discussion (FGD). Total of 67 species consist of 62 genera and 32 families are recognized and utilized as medicinal plants by people of Tribe Serawai. The part of plant that are mostly used in Serawai’s medicine is leaves. Other parts that used for the medicine are fruits, roots, barks, and seeds. The medicinal plants of Serawai are applied for curative agent and additives material. Most of the traditional medicine of Serawai Tribe are taken by  rubbing, the others are used by oral, dropping and suppository. The LUVI of Serawai’s medicinal plants are range from 0.01% to 0.32%, the highest LUVI was obtained  by a crops plants.